Experimental and analytical studies on earthquake resisting behaviour of confined concrete block masonry structures. - Hori, Norio
To improve the seismic performance of masonry structures, confined masonry that improves the seismic resistance of masonry structures by the confining effect of surrounding bond beams and tie columns is constructed. This study investigated the earthquake resisting behaviour of confined masonry structures that are being studied and constructed in China. The structural system consists of unreinforced block masonry walls with surrounding reinforced concrete bond beams and tie columns. The characteristics of the structure include: (1) damage to blocks is reduced and brittle failure is avoided by the comparatively lower strength of the joint mortar than that of the blocks, (2) the masonry walls and surrounding reinforced concrete bond beams and tie columns are securely jointed by the shear keys of the tie columns. In this study, wall specimens made of concrete blocks were tested under a cyclic lateral load and simulated by a rigid body spring model that models non-linear behaviour by rigid bodies and boundary springs. The results of studies outline the resisting mechanism, indicating that a rigid body spring model is considered appropriate for analysing this type of structure.
Keywords: Confined masonry structure; Concrete block; Mortar joint; Earthquake resistance; Static load test; Rigid body spring model